Proposal for Prototyping Disruptive Self-Sufficient Power Engines: Harnessing "Pull" Forces - Ferreiro Garcia, Ramon (JOURNAL OF ADVANCES IN PHYSICS, 2025)
It is widely accepted that energy cannot be created from nothing, but must be transformed in accordance with the laws of conservation. Nonetheless, experimental evidence suggests that useful mechanical work can be generated not only by adding heat but also by extracting it. This process creates a vacuum that produces traction forces, which in turn can yield mechanical work—potentially paving the way for self-sufficient power engines. This article explores plausible technological pathways based on traction or pulling forces, which have been largely overlooked in conventional thermodynamic systems. These forces can be induced by cooling a thermal working fluid, generating vacuum without direct energy input. Achieving a truly self-sufficient heat engine would require rethinking or even challenging foundational principles of thermodynamics, including the conservation of energy, the first law of thermodynamics, Carnot’s theorem, and the concept of exergy. In fact, this proposal undergoes a feasible disruptive path toward Self-Sufficient Power Engines (SSPE). The best result among four cases studied consists of a self-sustaining power plant (SSPE) composed of a cascade of nine Power Units (PUs) that provide a self-sufficiency index of 250 with respect to a reference of 100 and a net electrical power of 597 (kJ/kg) per cycle.